Interdisciplinary legal studies the next generation - Sarat, Austin (Bingley, UK : Emerald, 2010)
This volume of Studies in Law, Politics, and Society brings together research by graduate students from universities in the United States and the United Kingdom. The work of these students was singled out by their teachers and advisors as showing unusual promise and marking out directions for the next generationA" of interdisciplinary legal scholars. The research collected here is often comparative. It is theoretically informed and rigorous in its methods. Taken together it shows breadth and excellence, and it signals the continuing vibrancy of interdisciplinary legal studies.
"Hybrid" justice at the Special Court for Sierra Leone / Sara Kendall -- Surviving property : resistance against urban housing nationalization during the transformation to communism (Romania, 1950-1965) / Mihaela Serban Rosen -- Disciplinary evolution of Turkish prisons, 1980s-1990s / Arda Ibikoglu -- "I'm Gonna Call My Lawyer" : shifting legal consciousness at the intersection of inequality / Diana Hernández -- A more global court? : a call for a new perspective on judicial globalization and its effect on the U.S. Supreme Court / Angela Narasimhan -- The sovereign city? : negotiating self-determination in an American military enclave / Erin E. Fitz-Henry -- Technique and technology in the kitchen : comparing resistance to municipal trans fat and foie gras bans / Michaela DeSoucey and David Schleifer -- Indigeneity : before and beyond the law / Kathleen Birrell.
Description based on print version record.
Keywords: Sociological jurisprudence; Law and the social sciences; Law & society; Courts & procedure; Law -- General; Law -- Trial Practice